Music Therapy - Yarashev Jurabek Turayevich (Research Parks Publishers, 2021)
In the article Art therapy, types of art therapy and harmonizing the mental state of a person through the development of self-knowledge and self-knowledge through music therapy, the importance of the use of art for therapeutic purposes is that art therapy it is used to express and study different feelings and emotions on a symbolic level